Featured Cover (Applied cognitive psychology, 2023)
The cover image is based on the Special Issue Article Understanding why searching the internet inflates confidence in explanatory ability by Emmaline Drew Eliseev and Elizabeth J. Marsh, https://doi.org/10.1002/acp.4058.